PENGEMBANGAN SISTEM INFORMASI PORTAL DOSEN BERBASIS WEB DI INSTITUT PENDIDIKAN INDONESIA GARUT - Fajar Maulana (Kohesi: Jurnal Sains dan Teknologi, 2023)
In campus academic activities, filling in KRS, student attendance, lecture schedules, exam schedules, value input and at the Indonesian Education Institute specifically for lecturers is still ongoing. Filling in manually using paper first by the lecturer is then collected to the study program which will then be returned to the data manager. each study program, giving rise to several processes such as input being carried out repeatedly, another example is the frequent drop in grades and lost grades experienced by some students, with a Web-Based Information System enabling very easy development and could be the answer to some of the problems above are because they were created for development according to needs, apart from that you can use backups for several servers using the latest system and are easy to develop. This will be the answer to make management easier even when changing developers because anyone can develop it, so on the basis of the above the author concludes It is necessary to create a page that can be integrated with existing information systems, including lecturers having an accurate database that can be accessed at any time for lecturers' needs or lecturers' needs for students without having to access central data first and is integrated directly with existing information systems.